Plant-based dietary index and body weight in people with type 1 diabetes: a secondary analysis of a randomized clinical trial - Kahleova, Hana; Fischer, Ilana; Smith, Reagan; Himmelfarb, Joseph; Znayenko-Miller, Tatiana; Holubkov, Richard; Barnard, Neal D. (Frontiers in Nutrition, 2025)
ObjectiveThis secondary analysis tested the relationship of a plant-based diet index (PDI), healthful PDI (hPDI), and unhealthful PDI (uPDI), with weight loss in adults with type 1 diabetes.MethodsFifty-eight adults with type 1 diabetes were randomized to follow an ad libitum low-fat vegan (n = 29) or a portion-controlled, energy-restricted diet (n = 29) for 12 weeks. Food records were analyzed and PDI indices were calculated. A repeated measure ANOVA, Spearman correlations, and a linear regression model were used for statistical analysis.ResultsThe PDI score increased on the vegan diet (p < 0.001) from 51.8 to 60.4, and did not change on the portion-controlled diet [effect size +6.0 (95% CI + 1.0 to +10.9); p = 0.02]; the hPDI increased on both diets, more on the vegan diet [effect size +9.1 (95% CI + 3.7 to +14.5); p = 0.002]; and uPDI increased on the vegan diet, and did not change on the portion-controlled diet [effect size +7.3 (95% CI + 1.9 to +12.7); p = 0.01]. Changes in PDI and hPDI scores correlated with changes in body weight [r = −0.35; p = 0.04 for PDI; and r = −0.52; p = 0.001 for hPDI], even after adjustment for changes in energy intake [r = −0.37; p = 0.04 for PDI; and r = −0.53; p = 0.001 for hPDI]. An increase in hPDI by 6.1 points was associated with a 1-kg weight loss (p = 0.01). There was no association between the changes in uPDI and changes in body weight (r = −0.07; p = 0.68).ConclusionThe study results suggest that replacing animal foods with plant foods is an effective strategy for weight loss in adults with type 1 diabetes. The inclusion of “unhealthy” plant-based foods did not impair weight loss, and these benefits were independent of energy intake.Clinical trial registrationClinicalTrials.gov, identifier NCT04944316.